PERUBAHAN PENGATURAN PERJANJIAN KERJA HARIAN DI INDONESIA DITINJAU DARI TEORI KEADILAN - Amany, Nailul (Refleksi Hukum: Jurnal Ilmu Hukum, 2023)
The provisions of the Daily Work Agreement (DWA) in Indonesia have the most significant change after the enactment of Act No. 11 of 2020 on Jobs Creation. By using the statute and historical approach, this article concludes: DWA has the most significant change on GR No. 35 of 2021, where DWA is expressly stated as one of the types of Specified Period Work Agreement (SPWA), but not all the rights of PKWT workers can easily be obtained by DWA workers. Based on John Rawls’ Theory of Justice, the current provisions on DWA in Indonesia do not reflect justice. Based on the grammatical interpretation theory with a contextualism approach, the rights of DWA workers should be the same as PKWT workers in general. However, based on systematic interpretation theory, DWA workers may lose their rights. Therefore, a complete understanding of the rights of DWA workers is needed by prioritizing the perspective of justice.